2007
DOI: 10.1002/pssa.200622516
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale surface characterization of GaN nanowires correlated with metal contact characteristics

Abstract: Surface electronic properties of GaN nanowires have been investigated using scanning probe microscopy and correlated with metal/nanowire contact characteristics. Surface current map of the nanowire was observed to be highly nonuniform, resulting from a large variation in surface barrier of the nanowire, on the order of a few tenths of an eV. The surface barrier non‐uniformity, which most likely determines the formation of an ohmic or Schottky contact, is increased dramatically with the nanowire surface deforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…3, with different conduction types existing in the same CZT sample. These phenomena agree with the previous report, 9 claiming that the conduction types of the Cd 1-x Zn x Te crystals grown with excess Te is dominated by the Zn composition; Below an x value of 0.07, the crystals are n type, but above this value, they are p type. This proposition is valid since it is in agreement with the fact the undoped CZT without Zn is n-type.…”
Section: Resultssupporting
confidence: 93%
“…3, with different conduction types existing in the same CZT sample. These phenomena agree with the previous report, 9 claiming that the conduction types of the Cd 1-x Zn x Te crystals grown with excess Te is dominated by the Zn composition; Below an x value of 0.07, the crystals are n type, but above this value, they are p type. This proposition is valid since it is in agreement with the fact the undoped CZT without Zn is n-type.…”
Section: Resultssupporting
confidence: 93%
“…They too found evidence of formation of an insulating interfacial layer at the contact region leading to non‐negligible formation of built‐in potential, causing a significant shift in the forward‐bias threshold voltage. In a related study on GaN NWs contacted with Ti/Al metal without annealing, Koley et al observed both Schottky‐ and Ohmic‐contact formation by measurements performed over many devices 33. In their study, the reported Schottky contacts were formed only on one of the two contacts producing asymmetric current–voltage ( I – V ) behavior.…”
Section: Semiconductor‐nw–metal‐contact Interfacial Propertiesmentioning
confidence: 99%
“…On the other hand, Ti, Cr, and Au have been used to form Schottky diodes [7,12]. These reports also demonstrate that the condition of the NW surface [5,6] and the size of the GaN nanowire [10] can affect the characteristics of the contact.…”
Section: Introductionmentioning
confidence: 92%
“…Researchers have reported the formation of both Schottky and ohmic contacts to GaN NWs. Sometimes a contact such as Ti/Al [5] has been observed to form either Schottky or ohmic contacts as a result of nonuniformities in the NW surface. The metallizations Ti/Al/Pt/Au [6], Ti/Au [7,8], Ni/Au [9], as well as Pt deposited by a focused ion beam [10,11], have all been successfully used to form Ohmic type contacts to n-type GaN nanowires, sometimes with the assistance of annealing or premetallization ultraviolet (UV) ozone surface treatments.…”
Section: Introductionmentioning
confidence: 99%